2009
DOI: 10.1097/iae.0b013e3181a94f01
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Injection of Therapeutic Agents

Abstract: The IVI technique is a valuable tool that can be tailored to the disease process of interest based on the pharmacological agent selected. This review provides the reader with a comprehensive summary of the IVI technique and its multitude of uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
126
0
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(142 citation statements)
references
References 444 publications
1
126
0
15
Order By: Relevance
“…[25][26][27][28]66 The advantages of intraocular injection are that high concentrations of drug can be achieved near the target tissue while minimizing systemic adverse effects. 66 However, repeated intraocular injection significantly increases the risk of ocular complications, including discomfort or pain, subconjunctival or vitreal hemorrhage, acute and sterile intraocular inflammation, uveitis, and endophthalmitis. 66,67 Reviews of clinical trials and patient charts to determine the safety of AMD intravitreal therapies have found that incidence rates for endophthalmitis range from 0 to 0.16%.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28]66 The advantages of intraocular injection are that high concentrations of drug can be achieved near the target tissue while minimizing systemic adverse effects. 66 However, repeated intraocular injection significantly increases the risk of ocular complications, including discomfort or pain, subconjunctival or vitreal hemorrhage, acute and sterile intraocular inflammation, uveitis, and endophthalmitis. 66,67 Reviews of clinical trials and patient charts to determine the safety of AMD intravitreal therapies have found that incidence rates for endophthalmitis range from 0 to 0.16%.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the chronic nature of the disease and short intravitreal half-life of bevacizumab (5), frequent intravitreal injections are indicated to maintain therapeutic concentrations at the retina/choroid. Such frequent administrations are inconvenient and cause potential ocular complications such as endophthalmitis, retinal detachment, retinal hemorrhage and, more importantly, patient noncompliance (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Intravitreal injections are widely used nowadays as an inoffice procedure to deliver anti-infectious, anti-inflammatory, anticancer, anti-VEGF medications, as well as gas into the eye (1). One of the most common side effects due to this treatment is discomfort or pain at the site of injection.…”
Section: Introductionmentioning
confidence: 99%